Measurement-based Characterization of Physical Layer Security for RIS-assisted Wireless Systems - Kesir, Samed; Kayrakhk, Sefa; Wikelek, Ibrahim; Pusane, Ali Emre; Basar, Ertugrul; Gorcin, Ali (IEEE, 2023)
There have been recently many studies demonstrating that the performance of wireless communication systems can be significantly improved by a reconfigurable intelligent surface (RIS), which is an attractive technology due to its low power requirement and low complexity. This paper presents a measurement-based characterization of RISs for providing physical layer security, where the transmitter (Alice), the intended user (Bob), and the eavesdropper (Eve) are deployed in an indoor environment. Each user is equipped with a software-defined radio connected to a horn antenna. The phase shifts of reflecting elements are software controlled to collaboratively determine the amount of received signal power at the locations of Bob and Eve in such a way that the secrecy capacity is aimed to be maximized. An iterative method is utilized to configure a Greenerwave RIS prototype consisting of 76 passive reflecting elements. Computer simulation and measurement results demonstrate that an RIS can be an effective tool to significantly increase the secrecy capacity between Bob and Eve.
Keywords: reconfigurable intelligent surface; physical layer security; practical measurements; Automation & Control Systems; Engineering